2017
DOI: 10.1530/erc-17-0009
|View full text |Cite
|
Sign up to set email alerts
|

A role for TET2 in parathyroid carcinoma

Abstract: Primary hyperparathyroidism (pHPT) is rarely caused by parathyroid carcinoma (PC, <1-5% of pHPT cases). The TET proteins oxidize the epigenetic mark 5-methylcytosine to 5-hydroxymethylcytosine (5hmC) and inactivation by mutation or epigenetic deregulation of and play important roles in various cancers. Recently, we found that 5hmC was severely reduced in all of the analyzed PCs and with deranged expression of TET1 for the majority of PCs. Here, we have examined the expression of the TET2 protein in 15 5hmC-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…At a functional level, the restoration of TET2 activity in the LN229 glioblastoma cell line reduced cell proliferation in vitro , and tumor growth in vivo , which is in agreement with previous work suggesting that TET2 has antitumor activity in leukemias [ 21 , 54 ] and in other types of tumors including parathyroid carcinoma [ 55 ], colorectal cancer [ 20 ] and glioma [ 53 ]. These results, then, suggest that TET2 activity is frequently disrupted in cancer through different molecular mechanisms and that this process might contribute to malignant transformation.…”
Section: Discussionsupporting
confidence: 90%
“…At a functional level, the restoration of TET2 activity in the LN229 glioblastoma cell line reduced cell proliferation in vitro , and tumor growth in vivo , which is in agreement with previous work suggesting that TET2 has antitumor activity in leukemias [ 21 , 54 ] and in other types of tumors including parathyroid carcinoma [ 55 ], colorectal cancer [ 20 ] and glioma [ 53 ]. These results, then, suggest that TET2 activity is frequently disrupted in cancer through different molecular mechanisms and that this process might contribute to malignant transformation.…”
Section: Discussionsupporting
confidence: 90%
“…3c ). Neither transfection with TET2 CRISPR double nickase plasmids [ 29 ] nor TET2 shRNAs resulted in efficient knockout of TET2 expression (data not shown).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The TET2 protein is a critical regulator of DNA hydroxymethylation. In recent years, TET2-induced DNA hydroxymethylation has been associated with critical regulation of the molecular pathogenesis of various diseases (11,24,25). Immune responses related to Thelper-cell differentiation are regulated by epigenetic changes (26).…”
Section: Discussionmentioning
confidence: 99%
“…2D). Previous studies have indicated that TET2 acts as a key epigenetic regulator (11,12). We next explored the expression levels of TET2 in the lesional skin of mice.…”
Section: Knockdown Of Tet2 Alleviated the Morphological And Histologimentioning
confidence: 99%
See 1 more Smart Citation